Asset Liability Management and Commercial Banks’ Profitability in Nepal - Shrestha, Sanjay (Academic Voices: A Multidisciplinary Journal, 2016)
This study examines the effect of ALM on commercial banks’ profitability in Nepal. ALM deals with the optimal investment of assets in view of meeting current goals and future liabilities. For this purpose top seven private commercial banks were taken as sample, which constitutes 49 percent share of total net profit of overall 30 commercial banks over 7 years time period from 2007-08 to 2013-14. The report emphasizes that the rate of return on assets is positive and varies across assets, and the rate of cost on liabilities is negative and varies across liabilities. The pooled OLS regression analysis result showed that all assets, including fixed assets, mainly loans and advances as well as other assets affect profitability positively, while all liabilities, mainly deposits, and other liabilities have negative effect on commercial banks profitability. With regard to macroeconomic variables, GDP and Inflation rate has negative effect on commercial banks profitability. As a result, the study recommended that commercial banks should focus on increasing public awareness to mobilize more saving and fixed deposits and this will enhance their performance in provision of loans and advance to customers. Academic Voices Vol.5 2015: 40-47